PENGARUH PEMANFAATAN MEDIA SOSIAL TERHADAP MINAT MENDAFTAR PENERIMAAN MAHASISWA BARU DI IAIN MANADO - Anis Fitrohatin (AL-IDZAAH: Jurnal Dakwah dan Komunikasi, 2025)
At IAIN Manado, using social media has become an inevitable strategy to ensure that information related to new student admissions is effectively conveyed to prospective students. An analysis of the usefulness of social media in the socialization of new student admissions needs to be conducted to gain a more accurate understanding of how well prospective students absorb and comprehend the information. It can provide a solution to determine the effectiveness of social media outreach at IAIN Manado. This research uses a quantitative method with an associative analysis approach, while the data analysis utilizes multiple linear regression. Four prerequisite stages for hypothesis testing are carried out to perform this test: data normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The calculation result shows R² = 0.817, indicating that the use of social media platforms such as Facebook, Instagram, and WhatsApp significantly influences the interest in registering for new student admissions at IAIN Manado. The result demonstrates that 81.7% of the interest in registering for new student admissions at IAIN Manado is determined or influenced by the use of Facebook, Instagram, and WhatsApp, while other variables influence the remaining 18.3%.